Depression, Anxiety and Stress among Undergraduate Students of Shah Abdul Latif University, Khairpur: Depression, Anxiety and Stress among Students - Jamali, Yasir Abkar; Khan, Jawad Ahmad; Jamali, Imran Ali; Shah, Hanozia; Jeetendar, .; Kumari, Ravina (Pakistan Journal of Health Sciences, 2024)
Higher rates of stress, anxiety, and depression are seen among university students. Objective: To find out the prevalence of stress, anxiety, and depression among undergraduate students. Methods: This was a cross-sectional survey study. The study was conducted among undergraduate students of Shah Abdul Latif University, Khairpur. The Depression Anxiety Stress Scale (DASS-21) was distributed to undergraduates in their first through last year of university. 132 students completed the DASS survey. We used Fisher’s exact tests to compare the variations between the student groupings. Results: There were 132 students in all, and their mean age was 20.75 ± 2.1 years. The participants were categorized into two age groups: the first age group consisting of those aged 17-19 years, accounting for 63 (47.7%), and the second age group including individuals aged 20-22 years, representing 69 (52.3%). The male students were represented by 75 (56.8%), while the female students were represented by 57 (43.2%). Over 82 (62.1%) of students had a poor socioeconomic status. Conclusions: Female students were found with high frequency of depression, stress and anxiety.